PENGELOLAAN BARANG KEBUTUHAN KITCHEN DI HOTEL GRAND ZURI PADANG - Naserd, Yolanda Febriani; Yuliana, Yuliana; Waryono, Waryono (Journal of Home Economics and Tourism, 2015)
This study aims to determine the management of kitchen necessities at Hotel Grand Zuri Padang. This research is a descriptive study using qualitative data with survey method. The sampling technique in this research is purposive sampling. This study consists of four indicators, namely management: Planning related to the objective to be achieved is to meet the needs of the guests at meal times, so that kitchen operations run smoothly and achieve the revenue targets that have been set hotel. Organizing related to the work to be done in managing the goods that check stock in chiller and banquet event order to know the event, an order item, perform an examination of the goods that come, and storage of goods into the chiller. The briefing conducted by chef and chef sake done by way of coordination and control. Control of inventory management is done by the chef needs kitchen and for the chef by controlling the way employees work, ensuring that the work is progressing in accordance with the Standard Operating Procedure (SOP) and guidebooks that have been granted to employees.Keywords: management, stock, kitchen1 Prodi D4 Manajemen Perhotelan untuk wisuda periode September